2014
DOI: 10.1513/annalsats.201405-225oc
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Echocardiographic Pulmonary Hypertension in Individuals with Human Immunodeficiency Virus–Hepatitis C Virus Coinfection

Abstract: Rationale: Human immunodeficiency virus (HIV) infection is a risk factor for pulmonary hypertension (PH). Chronic hepatitis C virus (HCV) infection may have unique or synergistic effects on the pulmonary vasculature, but the prevalence and risk factors for PH in HIV-HCV coinfected persons are not known.Objectives: To define the prevalence of echocardiographic PH in a cohort of patients with HIV-HCV coinfection, to compare this estimate with the reported prevalence of PH among those with HIV infection alone, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 46 publications
1
23
0
2
Order By: Relevance
“…In a recent study, a preliminary prevalence of echocardiographic PAH in HIV-HCV was considerably higher than that reported for HIV alone. Moreover, time since HCV diagnosis and treatment of HCV with interferon were both significantly associated with the development of PAH and right ventricular dysfunction as assessed by echocardiography [112]. Accordingly, the prevalence of echocardiographic PAH may be higher in HIV-HCV co-infected patients than in those with HIV mono-infection alone, a contention that deserves further investigation as potential aetiology of pulmonary vascular disease.…”
Section: Current Status Of Pophmentioning
confidence: 98%
“…In a recent study, a preliminary prevalence of echocardiographic PAH in HIV-HCV was considerably higher than that reported for HIV alone. Moreover, time since HCV diagnosis and treatment of HCV with interferon were both significantly associated with the development of PAH and right ventricular dysfunction as assessed by echocardiography [112]. Accordingly, the prevalence of echocardiographic PAH may be higher in HIV-HCV co-infected patients than in those with HIV mono-infection alone, a contention that deserves further investigation as potential aetiology of pulmonary vascular disease.…”
Section: Current Status Of Pophmentioning
confidence: 98%
“…On bedside finding, new clinical risk factors will be investigated to know better the role of INF (a, b) in particular subgroups (chronic hepatitis C coinfection with portal hypertension) [101]. In fact in a recent study, INF treatment, as well as time since HCV diagnosis, has been associated with the development of PH assessed by echocardiography in HIV patients [102] However, there is an important need of pharmacological specific multicentre trial designed for HIV-PAH patients to evaluate the best therapy for these subjects.…”
Section: Future Developmentmentioning
confidence: 99%
“…The high prevalence of HF and COPD in particular likely contributes to the relative high prevalence of echocardiographic PH in our cohort; however, our statistical models account for these comorbidities, among others. Another retrospective analysis using clinically-indicated studies reported a prevalence of PH or RV dysfunction of 26% 5 . Ours is the largest (by an order of magnitude) echocardiographic cohort to examine specific HIV and HCV viral markers and PASP as continuous variables.…”
Section: Discussionmentioning
confidence: 99%